2020
DOI: 10.7717/peerj.10245
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of APLN and APELA in the physiology and pathology of the female reproductive system

Abstract: APLN, APELA and their common receptor APLNR (composing the apelinergic axis) have been described in various species with extensive body distribution and multiple physiological functions. Recent studies have witnessed emerging intracellular cascades triggered by APLN and APELA which play crucial roles in female reproductive organs, including hypothalamus-pituitary-gonadal axis, ovary, oviduct, uterus and placenta. However, a comprehensive summary of APLN and APELA roles in physiology and pathology of female rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 101 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…In the current study, we revealed that APELA supports the self-renewal of GSCs and negatively regulates cAMP-induced neuronal differentiation. APELA inhibits differentiation probably by suppressing the activity of adenylate cyclase that catalyzes the conversion of ATP to cAMP [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we revealed that APELA supports the self-renewal of GSCs and negatively regulates cAMP-induced neuronal differentiation. APELA inhibits differentiation probably by suppressing the activity of adenylate cyclase that catalyzes the conversion of ATP to cAMP [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that APJ silencing in apelin‐overexpression lung cancer cells did not completely inhibit apelin‐mediated cell proliferation. Although APJ is the only known receptor for apelin, it remains possible that apelin might act in lung cancer cells by another signaling pathway 38,39 . Apelin‐induced activation of APJ suppresses the expression of active SREBP1 and lipid accumulation in hepatocytes 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Although APJ is the only known receptor for apelin, it remains possible that apelin might act in lung cancer cells by another signaling pathway. 38 , 39 Apelin‐induced activation of APJ suppresses the expression of active SREBP1 and lipid accumulation in hepatocytes. 40 These research results imply a functional role of the apelin‐APJ receptor complex in inhibiting adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the involvement and role of adipokines are emerging to the forefront in the field of fertility and reproduction. Many studies suggested that adipokines such as leptin (Spicer, 2001; Tersigni et al, 2011), visfatin (Annie et al, 2020; Reverchon et al, 2013), resistin (Maillard et al, 2011; Niles et al, 2012; Reverchon et al, 2013), adiponectin (Chabrolle et al, 2007; Ledoux et al, 2006; Lord et al, 2005; Schmidt et al, 2008; Takemura et al, 2006), chemerin (Carlino et al, 2012; Goralski et al, 2007; Reverchon et al, 2012) and apelin (Kurowska et al, 2018; Roche et al, 2016; Shokrollahi et al, 2022; Wang et al, 2020) are expressed and play important role in ovary, uterus, placenta. Apelin is expressed in various types of tissues and organs such as the central nervous system and peripheral tissues, including the hypothalamus, adipose tissue, skeletal muscle, digestive system, ovary, uterus, placenta and mammary gland (Cobellis et al, 2007; Mercati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of apelin/APJ in granulosa cells, thecal cells and luteal cells of ovary in bovine (Shimizu et al, 2009) and ewes (Mercati et al, 2019) have shown to be elevated with follicular growth. It has been shown that apelin regulates steroidogenesis of granulosa cells and corpus luteum, as an auto/paracrine factor (Różycka et al, 2018;Shokrollahi et al, 2022;Wang et al, 2020). It has also been shown that apelin regulates steroidogenesis via 3β HSD, AMPKa activation and Akt and MAPK3/1 signaling (Rak et al, 2017;Roche et al, 2016Roche et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%